A corporate strategy for Hongkong Bank - Bacani, Ma. Lourdes E. (Animo Repository, 1997)
INDUSTRY PROFILE. The Hongkong and Shanghai Banking Corporation Limited, usually known as Hongkong Bank, belongs to the financial services industry. This industry has been defined as a group of companies engaged in providing services relating to the management of money and other financial assets, banking, investments, credits of individuals and companies.